Motorik Kasar Anak Usia Dini - Nurul Arifiyanti; Rifka Fitriana; Rina Kusmiyati; Novi Kurnia Sari; Siti Usriyah (STAINU Purworejo, 2019)
Physical development is one of the core component for achieving the next level. When the child’s physical develop well, they can develop by themself. This paper is a literature review which try to discuss about early childhood, gross motor, gross motor’s level, factor, and the benefit.